PATHOGENESIS OF PERIODONTAL DISEASE - Soares, Kaio Henrique; Martins, Olga Beatriz Lopes; Leite, Mariana Botelho; Alves, Sâmia Francy Ferreira; Lopes, Maria Rita Lima; Santos, Jefferson Aguiar; Paulino, Gabriela Leite; Soares, Célio Leone Ferreira (Seven Editora, 2026)
The pathogenesis of periodontal disease results from the complex interaction between a dysbiotic microbial biofilm and the host's immune-inflammatory response, with chronic inflammation being the main mechanism responsible for the destruction of periodontal tissues. Disease progression occurs from gingivitis to periodontitis, involving attachment loss, bone resorption, and eventual tooth loss, mediated by bacterial virulence factors and the release of inflammatory cytokines and destructive enzymes. Furthermore, systemic, genetic, behavioral, and local risk factors modulate the susceptibility and severity of the disease, reinforcing the importance of therapeutic strategies aimed at biofilm control, modulation of the inflammatory response, and long-term periodontal maintenance.